Do migrant remittances matter for financial development in Kenya? - Roseline Nyakerario Misati; Anne Kamau; Hared Nassir (Financial Innovation, 2019)
The paper analyzes the relationship between remittances and financial development using Kenyan quarterly data from 2006 to 2016. Five different indicators of financial development are used: credit to the private sector as a share of GDP, the number of mobile transactions, the value of these mobile transactions, the number of mobile agents, and the number of bank accounts. The results from using an autoregressive distributed lag demonstrate a strong, positive relationship between remittances and financial development in long-run equations. This suggests that higher levels of remittances provide opportunities for recipients to open bank accounts, enhance their savings, and access financial systems, in addition to exposing the previously unbanked to both new and existing financial products. The results also confirm the potential advantage of embracing modern and advanced technology to facilitate international mobile transfers. Using international remittance transfers through mobile technology reduces costs by eliminating the need for physical branches and personnel to attend to walk-in customers. Aside from offering convenience and safety for remittance actors, this method also dominates traditional remittance business models. Therefore, a policy window exists for the government to leverage on remittances as a tool of financial inclusion and depth, and particularly through the continued expansion of regulatory space to accommodate the wider use of international mobile remittance transfer channels. Moreover, given the strong, positive relationship between remittances and credit to the private sector as indicated by its share of GDP and number of bank accounts, commercial banks and other players in the remittance market may also find it useful to develop customized products for migrants to access their remittances. For example, financial intermediaries can consider providing better deposit interest rates for diaspora deposits compared to deposits made in the local currency. Further, these institutions can allow regular remittance flows to act as collateral for the allocation of credit, among other incentives to tap into the significant potential of money remitted by migrants to Kenya. The study also recommends that the government consider expanding exploitation of diaspora bonds and diaspora savings and credit cooperative societies while drawing lessons from other countries' previous attempts.
Keywords: 650; Remittances; Financial inclusion; Technology